2010
DOI: 10.1038/aps.2010.72
|View full text |Cite
|
Sign up to set email alerts
|

Withagulatin A inhibits hepatic stellate cell viability and procollagen I production through Akt and Smad signaling pathways

Abstract: Aim: To investigate the effects of the natural product Withagulatin A on hepatic stellate cell (HSC) viability and type I procollagen production. The potential mechanism underlying the pharmacological actions was also explored. Methods: The effect of Withagulatin A on cell viability was evaluated in HSC and LX-2 cells using a sulforhodamine B (SRB) assay. Cell cycle distribution was analyzed using flow cytometry. Type I procollagen gene expression was determined using real-time PCR. Regulation of signaling mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It was also observed that plumbagin sharply inhibited other signals, such as pSTAT3, NF-κB/p65, and Akt/mTOR in LX-2 cells (Figure 6B ), which all are involved in inflammation and liver fibrosis [ 21 25 ]. In addition, NF-κB/p65 activation in RAW 264.7 cells was decreased by plumbagin ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also observed that plumbagin sharply inhibited other signals, such as pSTAT3, NF-κB/p65, and Akt/mTOR in LX-2 cells (Figure 6B ), which all are involved in inflammation and liver fibrosis [ 21 25 ]. In addition, NF-κB/p65 activation in RAW 264.7 cells was decreased by plumbagin ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Akt/mTOR pathway correlates HSC survival and proliferation [ 22 24 ]. Activated Akt is a key survival factor that directly phosphorylates mTOR, which ultimately stimulates HSC proliferation [ 25 ]. STAT3 actively promotes HSC activation [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation was measured by standard sulforhodamine B (SRB) assays 27 and the optical density (OD) value was read at 515 nm using a multi-well spectrophotometer (VERSAmax, Molecular Devices). The growth inhibition rate was calculated as (OD 515control -OD 515agents )/OD 515control × 100%.…”
Section: Methodsmentioning
confidence: 99%
“… 25 A study on withagulatin A isolated from P. angulata L showed inhibition of TGF-β stimulated type I procollagen gene expression in primary hepatic stellate cells isolated from normal livers of male Sprague Dawley rats, which was attributable to the suppression of TGF-β stimulated SMAD2 and SMAD3 phosphorylation. 26 The expression of keloid procollagen 1 mRNA increased 35 times compared to preputium fibroblast. 6 Excessive collagen formation in keloid is the target therapy for keloid.…”
Section: Discussionmentioning
confidence: 99%